Climate-smart agriculture and the World Trade Organization - Glauber, Joseph W. (American Enterprise Institute, 2022)
Key Points Climate change threatens global food security and sustainable development, while many agricultural subsidies exacerbate environmental impact and agriculture’s carbon footprint around the world. Climate-smart agriculture (CSA) may provide frameworks for policy-based incentives to reduce agriculture’s greenhouse gas (GHG) emissions. Conceptually, CSA practices could be important tools to address the impact of a growing human population on the global environment, but providing large subsidies for selected production practices that have little impact on GHG emissions could conflict with international trade laws. Agricultural trade liberalization should be integral to any CSA approach because, globally, resources are likely to be used more efficiently.